2005
DOI: 10.1091/mbc.e04-12-1130
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Ubiquitin Ligase SCFMet30Regulates Heavy Metal Response

Abstract: Cells have developed a variety of mechanisms to respond to heavy metal exposure. Here, we show that the yeast ubiquitin ligase SCF Met30 plays a central role in the response to two of the most toxic environmental heavy metal contaminants, namely, cadmium and arsenic. SCF Met30 inactivates the transcription factor Met4 by proteolysis-independent polyubiquitination. Exposure of yeast cells to heavy metals led to activation of Met4 as indicated by a complete loss of ubiquitinated Met4 species. The association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 47 publications
7
79
0
Order By: Relevance
“…This putative pathway would activate the transcriptional activator Met4 since all the genes of the sulfur amino acid pathway are induced by cadmium in a Met4-dependent way (7). Consistent with our data, recent work showed that Met4, which is normally inactivated following methionine supplementation (through the increased pool of cysteine), remains active when methionine-supplemented cells are treated with cadmium (28,29). Under cadmium conditions, Met4 is stabilized as a result of the dissociation of the Skp1-Met-30 interaction in the SCF Met30 ubiquitin ligase complex (28) that targets the ubiquitylation and the degradation of Met-4 upon methionine addition (30).…”
Section: Protein and Metabolite Levels Can Be Positively Or Negativelsupporting
confidence: 88%
“…This putative pathway would activate the transcriptional activator Met4 since all the genes of the sulfur amino acid pathway are induced by cadmium in a Met4-dependent way (7). Consistent with our data, recent work showed that Met4, which is normally inactivated following methionine supplementation (through the increased pool of cysteine), remains active when methionine-supplemented cells are treated with cadmium (28,29). Under cadmium conditions, Met4 is stabilized as a result of the dissociation of the Skp1-Met-30 interaction in the SCF Met30 ubiquitin ligase complex (28) that targets the ubiquitylation and the degradation of Met-4 upon methionine addition (30).…”
Section: Protein and Metabolite Levels Can Be Positively Or Negativelsupporting
confidence: 88%
“…This implied connection is strengthened by a study of glucose repletion in yeast, which shows that methionine biosynthetic genes are highly induced upon relief from glucose starvation (8). The methionine-regulated transcription factors are also well known to regulate the response to various toxins, including heavy metals and oxidizing agents (9,10).…”
mentioning
confidence: 99%
“…Since the literature suggests that cadmium promotes disassembly of the SCF complex (Yen et al, 2012(Yen et al, , 2005, overexpression of SKP1 may reduce the degree of SCF complex disassembly following cadmium exposure, thereby leading to attenuation of cadmium toxicity. RPN8 is a gene encoding a non-ATPase regulatory subunit of the 26S proteasome (Finley et al, 1998), MES1 encodes a methionyl-tRNA synthetase (Chatton et al, 1987) and MIA40 encodes a mitochondrial oxidoreductase (Chacinska et al, 2004).…”
Section: Resultsmentioning
confidence: 99%